Closing the gap: training for healthcare workers and people with disabilities on the interrelationship of HIV and disability. (October 2015) - Hanass-Hancock, Jill; Alli, Farzana
Abstract Background: HIV and disability are interrelated providing a double burden to HIV endemic countries in East and Southern Africa and their already fragile health systems. Although literature reveals that people with disabilities are particularly vulnerable to HIV and that HIV, its opportunistic infections and treatments can cause disability, only few interventions target this issue and none have been evaluated in this region. Methods: Formative evaluation was undertaken with regard to the effectiveness of a workshop-based intervention for healthcare workers and people with disabilities on the intersection of disability and HIV in order to inform the further development of this intervention. The formative evaluation assessed participants' perception of the inclusion of disability in HIV services and of opportunities to initiate change after the workshops. It also captured their experiences in utilising knowledge and skills after the workshops using quantitative (short checklist and ranking exercise) and qualitative (semi-structured interviews) methods of inquiry. Frequencies and conventional content analysis were used in the analysis of the data. This study presents an example of applied research conducted under real-world conditions. Results: 60 healthcare workers and people with disabilities took part in this pilot workshop training and participated in the formative evaluation. Healthcare workers and people with disabilities alike identified various barriers to access health services. Reasonable accommodation was perceived as being mainly absent by most participants, while some participants indicated a lack of physical accessibility in the form of universal design. Participants also identified a lack of integration of services and disability-related skills within the healthcare staff. Participants reported a number of enablers, success and challenges while implementing the knowledge from the workshops related to structural issues, service provision and integration. While participants worked on health workers' attitudes and accessibility of services, screening and referrals practice was not improved through the workshops. Conclusions: Formative evaluation indicates that the workshops can be effective not only in sensitising healthcare workers and people with disabilities to opportunities to improve services for people with disabilities but also to provide knowledge and skills to initiate improvements. Skills that need more practical training (e.g. screening for disability) need to be trained in more detail, and this will inform the adaptation of the workshops. However, the workshop evaluation also revealed that without policy implementation and budget allocations this change would only be limited. Implications for Rehabilitation HIV, its co-morbidities and treatments cause health conditions and impairments that have the potential to develop into disability. People with disabilities are at increased risk of exposure to HIV. Rehabilitation professionals, healthcare workers and people with disabilities can be sensitised in a three-day workshop on the relationship of disability and HIV. However, the trained participants can only implement no or low-cost elements of interventions, while high-cost interventions need budget allocations at provincial and national level.